2021
DOI: 10.3390/cancers13205166
|View full text |Cite
|
Sign up to set email alerts
|

Pulmonary Nodule and Mass: Superiority of MRI of Diffusion-Weighted Imaging and T2-Weighted Imaging to FDG-PET/CT

Abstract: The purpose of this retrospective study was to compare the diagnostic efficacy of FDG-PET/CT and MRI in discriminating malignant from benign pulmonary nodules and masses (PNMs). There were 278 lung cancers and 50 benign PNMs that were examined by FDG-PET/CT and MRI. The T2 contrast ratio (T2 CR) was designated as the ratio of T2 signal intensity of PNM divided by T2 signal intensity of the rhomboid muscle. The optimal cut-off values (OCVs) for differential diagnosis were 3.605 for maximum standardized uptake v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 55 publications
0
4
0
Order By: Relevance
“…To the best of our knowledge, with the supplement of related important clinical characteristics, Model 3 based on arterial-venous-plain combined scan phase of CT has important clinical significance in distinguishing SCC from SCH. In conclusion, our results demonstrated that radiomics could provide valuable information and play an important role in preoperative diagnosis and clinical treatment to guide clinicians to develop individualized treatment programs ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 62%
“…To the best of our knowledge, with the supplement of related important clinical characteristics, Model 3 based on arterial-venous-plain combined scan phase of CT has important clinical significance in distinguishing SCC from SCH. In conclusion, our results demonstrated that radiomics could provide valuable information and play an important role in preoperative diagnosis and clinical treatment to guide clinicians to develop individualized treatment programs ( 25 , 26 ).…”
Section: Discussionmentioning
confidence: 62%
“…Nevertheless, in a resource-constrained setting, the diffusion characteristics of a lesion in conjunction with its T2 signal can more than suffice to determine its malignant potential. 8 The concerns over inconsistencies in the evaluation of quantitative parameters as a result of magnetic field susceptibility artifacts at the lesion-air interface persist for this study. While some research articles have asserted to circumvent this pitfall through non-echoplanar diffusion imaging, additional research in this regard may provide more definitive answers.…”
mentioning
confidence: 99%
“…A chest MRI was then conducted (Figure 2), revealing diffusion restriction in the diffusion-weighted imaging (DWI) of the upper right lobe lesion. Empiric treatment with amoxicillin-clavulanic acid 1 g × 3 was initiated, resulting in gradual increase of body weight and diminution of One of the main utilities of diffusion-weighted MRI sequences is the differentiation of abscess from malignant mimicker (tumors with central necrosis) and thus they are broadly used in combination with ADC map, in brain and liver MRI [1][2][3] . Despite that both malignancy and abscess can restrict diffusion in diffusion-weighted MRI sequences, there are some distinct differences in the restriction pattern between them which can lead to the differential diagnosis 1,2 .…”
mentioning
confidence: 99%
“…Empiric treatment with amoxicillin-clavulanic acid 1 g × 3 was initiated, resulting in gradual increase of body weight and diminution of One of the main utilities of diffusion-weighted MRI sequences is the differentiation of abscess from malignant mimicker (tumors with central necrosis) and thus they are broadly used in combination with ADC map, in brain and liver MRI [1][2][3] . Despite that both malignancy and abscess can restrict diffusion in diffusion-weighted MRI sequences, there are some distinct differences in the restriction pattern between them which can lead to the differential diagnosis 1,2 . Abscesses manifest intense restricted diffusion in their cystic necrotic compartment, with high DWI signal and particularly low signal in ADC maps (usually <800 mm 2 /s).…”
mentioning
confidence: 99%